ChemInform Abstract: Ammonium Aminodiboranate: A Long‐Sought Isomer of Diammoniate of Diborane and Ammonia Borane Dimer. Issue 35 (August 2016) - Chen, Weidong; Yu, Haibo; Wu, Guotao; He, Teng; Li, Zhao; Guo, Zaiping; Liu, Huakun; Huang, Zhenguo; Chen, Ping
Abstract: Formation of [NH4 ][BH3 NH2 BH3 ] by metathesis reaction between Na(BH3 NH2 BH3 ) and NH4 SCN in a 1:1 molar ratio in THF at ‐18 °C is monitored by 11 B NMR spectroscopy.